SpPdp11 Administration in Diet Modified the Transcriptomic Response and Its Microbiota Associated in Mechanically Induced Wound Sparus aurata Skin - Cerezo Ortega, Isabel M.; Pérez-Gómez, Olivia; Bautista-Moreno, Rocío; Seoane Zonjic, Pedro; Esteban, María Ángeles; Balebona-Accino, María del Carmen; Moriñigo-Gutiérrez, Miguel Ángel; Tapia-Paniagua, Silvana Teresa (MDPI, 2023)
Skin lesions are a frequent fact associated with intensive conditions affecting farmed fish. Knowing that the use of probiotics can improve fish skin health, SpPdp11 dietary administration has demonstrated beneficial effects for farmed fish, so its potential on the skin needs to be studied more deeply. The wounded specimens that received the diet with SpPdp11 showed a decrease in the abundance of Enterobacteriaceae, Photobacterium and Achromobacter related to bacterial biofilm formation, as well as the overexpression of genes involved in signaling mechanisms (itpr3), cell migration and differentiation (panxa, ttbk1a, smpd3, vamp5); and repression of genes related to cell proliferation (vstm4a, areg), consistent with a more efficient skin healing processes than that observed in the wounded control group. In addition, among the groups of damaged skin with different diets, Achromobacter, f_Ruminococcaceae, p_Bacteroidetes, Fluviicola and Flavobacterium genera with significant differences showed positive correlations with genes related to cell migration and negative correlations with inflammation and cell proliferation and may be the target of future studies
Keywords: Peces - Microbiología; Shewanella putrefaciens Pdp11; Sparus aurata; Trasncriptomic; Skin microbiota